20 secrets to success for NCAA student-athletes - Burton, Rick (Ohio University sport management series., 2021)
"More than 99 percent of student-athletes will go pro in something other than sports. This book is for those college athletes (and their advisors and families). It provides advice and insights for the typical student-athlete on how to navigate the college experience and name, image, and licensing rights and to prepare for life after graduation"--